2017
DOI: 10.32007/med.1936/jfacmedbagdad.v59i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring of Plasma Melatonin Level in Patients with Preeclampsia

Abstract: Background: disturbed physiological rhythm of blood pressure in preeclampsia is a common finding. The role of oxidative stress in pathogenesis of preeclampsia is well accepted. Melatonin is a powerful free radical scavenger so it's rapidly consumed by enhanced reactive oxygen species in preeclampsia causing non-dipping in blood pressure. Objective: To evaluate the change in plasma melatonin levels in patients with preeclampsia and its relationship with blood pressure. Patients and methods: In this prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…), obesity, diabetes mellitus, metabolic syndrome, endometriosis and polycystic ovary syndrome, as well as in women working at night [ 138 , 139 , 140 , 141 , 142 , 143 ]. It has been found that in such women pregnancies are complicated by chronic placental insufficiency, preeclampsia and gestational diabetes [ 144 , 145 , 146 , 147 ]. Numerous experimental and clinical studies provide evidence that in the case of preeclampsia there is no significant increase in epiphyseal melatonin (which is characteristic for noncomplicated pregnancies) and no melatonin circadian rhythm [ 88 , 139 , 148 ].…”
Section: The State Of the Placenta And Fetal Development In The Camentioning
confidence: 99%
“…), obesity, diabetes mellitus, metabolic syndrome, endometriosis and polycystic ovary syndrome, as well as in women working at night [ 138 , 139 , 140 , 141 , 142 , 143 ]. It has been found that in such women pregnancies are complicated by chronic placental insufficiency, preeclampsia and gestational diabetes [ 144 , 145 , 146 , 147 ]. Numerous experimental and clinical studies provide evidence that in the case of preeclampsia there is no significant increase in epiphyseal melatonin (which is characteristic for noncomplicated pregnancies) and no melatonin circadian rhythm [ 88 , 139 , 148 ].…”
Section: The State Of the Placenta And Fetal Development In The Camentioning
confidence: 99%